High power laser system of a visible range with output XeF(C-A) amplifire - Losev V. F. Valery Fedorovich; Alekseev S. V. Sergey Vladimirovich; Ivanov N. G. Nikolay Georgievich; Ivanov M. V. Mikhail Vladimirovich; Mesyats G. A. Gennady Andreyevich; Mikheev L. D. Leonid Dmitrievich; Panchenko Yu. N. Yury Nikolaevich; Ratakhin N. A. Nikolay Aleksandrovich; Yastremsky A. G. Arkady Grigorjevich (2016, 2016)
Title screen